Water Quality Index of Different Areas in Calicut City - Joseph, Jesiamma; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
In the present study, the water samples during pre-monsoon, monsoon and post-monsoon for three consecutive years were taken and physicochemical parameters were analyzed. Water quality index has been calculated from the point of view of the suitability of surface and bore waters for human consumption.